2008
DOI: 10.2190/ag.66.3.e
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Experience regarding Hiv/Aids among Older Adult Inner-City Latinos

Abstract: Although Latinos, now the largest minority group in the U.S., comprise 13% of the population, they represent 18% of all new HIV and AIDS cases. This disproportionate representation also appears among older adult Latinos. Semi-structured interviews with 45 inner-city Spanish speaking older adult Latinos provide new data regarding HIV/AIDS among this largely ignored but at risk population. Findings indicate that approximately two thirds of the sample ascribed to at least one myth regarding viral transmission (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Important cultural factors have been associated with HIV risk behaviors among Latino men including stigma associated with HIV (Carballo-Dieguez, 1998; Pérez-Jiménez, Seal, & Serrano-García, 2009; Sanchez, 1998), stigmatized sexuality including traditional gender roles for women fueled by machismo (Anderson, Lopez, & Sorensen, 2001; Hillman, 2008; Lo, Reisen, Poppen, Bianchi, & Zea, 2011), and marianismo that promote risk behaviors as normative among men and relegate women to subservient positions to men in a traditional hierarchy (Doll, Petersen, White, Johnson, & Ward, 1992; Wood & Price, 1997). Furthermore, Latinos who have recently immigrated to the U.S. face issues associated with transience, a lack of formal education, undocumented immigration status, inadequate access to health insurance and quality health care, and low wages—all of which hinder their access to HIV prevention, screening, testing, and care (Garcia & Duckett, 2009; Hillman, 2008; Martinez et al, 2011; Rhodes, Hergenrather, Bloom, Leichliter, & Montaño, 2009).…”
Section: Hiv Among Latinos In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Important cultural factors have been associated with HIV risk behaviors among Latino men including stigma associated with HIV (Carballo-Dieguez, 1998; Pérez-Jiménez, Seal, & Serrano-García, 2009; Sanchez, 1998), stigmatized sexuality including traditional gender roles for women fueled by machismo (Anderson, Lopez, & Sorensen, 2001; Hillman, 2008; Lo, Reisen, Poppen, Bianchi, & Zea, 2011), and marianismo that promote risk behaviors as normative among men and relegate women to subservient positions to men in a traditional hierarchy (Doll, Petersen, White, Johnson, & Ward, 1992; Wood & Price, 1997). Furthermore, Latinos who have recently immigrated to the U.S. face issues associated with transience, a lack of formal education, undocumented immigration status, inadequate access to health insurance and quality health care, and low wages—all of which hinder their access to HIV prevention, screening, testing, and care (Garcia & Duckett, 2009; Hillman, 2008; Martinez et al, 2011; Rhodes, Hergenrather, Bloom, Leichliter, & Montaño, 2009).…”
Section: Hiv Among Latinos In the United Statesmentioning
confidence: 99%
“…Furthermore, Latinos who have recently immigrated to the U.S. face issues associated with transience, a lack of formal education, undocumented immigration status, inadequate access to health insurance and quality health care, and low wages—all of which hinder their access to HIV prevention, screening, testing, and care (Garcia & Duckett, 2009; Hillman, 2008; Martinez et al, 2011; Rhodes, Hergenrather, Bloom, Leichliter, & Montaño, 2009). Behavioral data also suggest that Spanish-speaking Latinos are disproportionately at risk for HIV compared to their English-speaking Latino and non-Latino counterparts (Rhodes et al, 2010; Wohl, Tejero, & Frye, 2009; Wolff & Ellis, 2009).…”
Section: Hiv Among Latinos In the United Statesmentioning
confidence: 99%
“…Research has shown 40% of older African American adults were uncertain about the effectiveness of condoms to protect one from STIs, with this uncertainty being even worse among women (Neundorfer, Harris, Britton, & Lynch, 2005;Rodgers-Farmer, 1999). Misconceptions about HIV and STI transmission are also common among older adults (Henderson et al, 2004;Hillman, 2007Hillman, , 2008Jackson, Early, Schim, & Penparse, 2005). For example, one 76-year-old African American man was quoted as stating, "he knows he's safe [from infections] as long as he pours Jack Daniels on his genitals immediately after sex" (Ward et al, 2011, p. 32).…”
Section: Background and Significancementioning
confidence: 99%
“…Future research could also investigate the impact of gender roles among Latina women who composed only a small percentage of women in our sample. Traditional gender norms such as marianismo (the belief that women should be self-sacrificing and defer to men as well as demonstrate loyalty and commitment to family needs; Denner & Dunbar, 2004; Ulibarri, Raj, & Amaro, 2012) and machismo (the expectation that men should control and dominate sexual relationships; Falicov, 2010) may potentially leave Latina women feeling powerless to negotiate safe sex practices and may increase HIV risk (Amaro & Raj, 2000; Hillman, 2008; Moreno, 2007; Tross, 2001; Ulibarri et al., 2012; Weidel, Provencio-Vasquez, Watson, & Gonzalez-Guarda, 2008). …”
Section: Discussionmentioning
confidence: 99%